Effect of knowledge and implemented practices of MSPO principle 6: best practice towards outcome gain among independent smallholder in Melaka / Taffa Azmizan Tahir - Tahir, Taffa Azmizan (Faculty of Plantation and Agrotechnology, 2018)
Malaysian Sustainable Palm Oil is certification that initiate by Malaysian Government and palm oil industry plays with certification by end of 2019. The study was carried out to study effect knowledge and implemented practice towards the outcome gain for group of certified independent smallholders, which Sustainable Palm Oil Cluster in Machap and Sungai Rambai. The data was taken from questionnaire basis and had been passed to 45 respondents in Machap and Sungai Rambai area. Results from the study reveal that correlation analysis, the knowledge and implemented practice has effect to the outcome gain. However, implemented practice is not influenced by the smallholders’ working experience. The recommendation, the next study should focus on the yield gain by smallholder and provide the data to any agency involve and is there something wrong with the certification, it can be improvise for the future of oil palm in Malaysia.